Traumatic Dental Injuries in Children and Adolescents from a Major Dental Clinic in Bosnia and Herzegovina: A 5-Year Retrospective Study - Olivera Dolic; Marija Obradovic; Zeljka Kojic; Natasa Knezevic; Natasa Trtic; Valentina Veselinovic; Marijana Arapovic-Savic; Mirjana Umicevic-Davidovic; Vanja Krcic (Medicina)
The aim of this study was to investigate the epidemiology of dental trauma in a public dental clinic in Banja Luka, Bosnia and Herzegovina, from 2019 to 2024. Methods: This research was conducted as a retrospective cross-sectional study. The data were analysed and compared between injured primary and permanent maxillary and mandibular teeth. Results: The review of the dental records revealed 73 patients (49 boys and 24 girls) with TDIs, involving 55 primary and 64 permanent teeth. Most of the patients (27 patients, 36.98%) were aged 7–9 years. The main cause of TDI was falls in both dentitions (81.81% of injured primary teeth and 73.43% of injured permanent teeth). The time of arrival after a TDI for assistance in the dental clinic for most cases was after 24 h in both dentitions, 45.45% of injured primary teeth and 48.43% of permanent teeth. For both dentitions, enamel fractures were the most common injury of hard dental tissues and the pulp, and the necrosis of the maxillary central incisor was the most common complication. Conclusions: It is very important to improve trauma management and increase public knowledge on the way parents seek proper treatment for the TDIs of their children, and in due time.